Peran Baitul Maal Wat Tamwil (BMT) Husnayain Terhadap Perkembangan Usaha Mikro Kecil dan dan Menengah - Sumardi Sumardi; Zulpahmi Zulpahmi (Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
This study aims to determine the role of Baitul Maal Wat Tamwil (BMT) Husnayain Against the Development of Micro Small and Medium Enterprises (UMKM). In the study used survey methods by taking samples from the population. The sample in this research is Baitul Maal Wat Tamwil (BMT) Husnayain customer, with 65 respondents. Data processing techniques and data analysis used are validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis test, and coefficient of determination. ttabel sebesar 1,998 dan signifikansi sebesar 0,004 < 0,05, sedangkan pembiayaan murabahah berpengaruh positif terhadap perkembangan usaha mikro